Efficacy of dimethyl fumarate in Japanese multiple sclerosis patients: interim analysis of randomized, double-blind APEX study and its open-label extension. Issue 3 (July 2019) - Kondo, T; Kawachi, I; Onizuka, Y; Hiramatsu, K; Hase, M; Yun, J; Matta, A; Torii, S
Background: Current data for the use of dimethyl fumarate (DMF) in Japanese patients with relapsing–remitting multiple sclerosis (RRMS) is limited. Objectives: To assess the efficacy of DMF in Japanese patients with RRMS. Methods: The phase 3, multinational APEX study (ClinicalTrials.gov identifier: NCT01838668) consisted of two parts: a 24-week double-blind part where subjects were randomized to receive DMF 240 mg or placebo twice daily in East Asian and Eastern European countries, and an open-label extension part where all subjects received DMF. The primary endpoint was the total number of new gadolinium-enhancing lesions in Weeks 12–24. In this interim analysis, we report efficacy data in the Japanese subgroup (DMF n = 56; placebo n = 58) over 72 weeks, including an extension phase. Results: DMF reduced the total number of new gadolinium-enhancing lesions in Weeks 12–24 by 85% versus placebo ( p < 0.0001). At Week 24, the annualized relapse rate was also reduced by 48% with DMF, versus placebo. DMF reduced the probability of relapse from Week 8 and was sustained. The number of gadolinium-enhancing lesions was maintained through 72 weeks. Conclusions: DMF demonstrated sustained efficacy in this Japanese subgroup. The results were consistent with those observed in studies of DMF enrolling primarily Caucasian patients.